Association of lung function with the risk of cardiovascular diseases and all-cause mortality in patients with diabetes: Results from NHANES III 1988-1994 - Huang, Nian; Tang, Chengyao; Li, Shiyang; Ma, Wenzhi; Zhai, Xiaobing; Liu, Keyang; Sheerah, Haytham A.; Cao, Jinhong (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objective: The potential effects of pulmonary dysfunction on cardiovascular diseases (CVD), and all-cause mortality are receiving attention. Current study aimed to explore whether reduced lung function is predicts CVD and all-cause mortality in diabetic people. Methods: 1723 adults with diabetes (mean age 60.2 years) were included from the National Health and Nutrition Examination Survey (NHANES III). Death outcomes were ascertained by linkage to the database records through 31 December 2015. Cox proportional hazards regression models were used to estimating hazard ratios (HRs) and 95% confidence intervals (CIs) for coronary heart disease (CHD), CVD, and all causes mortality. We conducted stratified analyses based on age, Body mass index (BMI), history of hypertension and dyslipidemia. Results: During a mean follow-up of 14.62 years (25,184 person-year), a total of 1,221 deaths were documented, of which were 327 CHD, 406 CVD, and 197 cancer, respectively. After multi-factor adjustment, participants with lower FEV1 and FVC had a higher risk of CHD, CVD, and all-cause mortality. And this association was also found in lower FVC and a higher risk of cancer mortality (HR: 3.85 (1.31-11.32); P for trend =0.040), but the association of FEV1 was attenuated after adjustment for covariates (HR:2.23 (0.54-9.17); P for trend =0.247). In subgroup analysis, we found that the adverse associations of FEV1 and FVC with CVD mortality were observed in subgroups of age, BMI, and history of hypertension and dyslipidemia. Conclusions: Declined lung function was associated with a higher risk of CVD and all-cause mortality in people with diabetes. Lung function tests, especially FEV1 and FVC, should be encouraged to provide prognostic and predictive information for the management of CVD and all-cause mortality in patients with diabetes. Key words：FEV1; FVC; CHD; CVD; Diabetes